1987
DOI: 10.1159/000184451
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Red-Stained Polyanionic Fixed Charges in Peritoneal Microvessels

Abstract: This study shows that the luminal surface of peritoneal microvascular endothelium, coated pits and coated vesicles are all negatively charged, unlike the limiting membrane of pinocytotic vesicles and transcellular channels. Our findings suggest that these cellular organelles have different functions as well as a different chemical composition. Anionic sites were observed along the subendothelial and subperithelial basal laminae of peritoneal capillaries and post capillary venules, respectively. Electric charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Although their physiological significance is less clear, the working hypothesis is that they retard the passage of molecules of similar charge a n d /o r accelerate that of molecules with opposite polarity. This is certainly true of anionic charges on glomerular and intestinal capillaries [5][6][7], Previous studies in our laboratory showed the exis tence of anionic charges on the peritoneal basement membrane and capillaries subjacent to it [8,9]. Recently we demonstrated that these charges are greatly reduced under conditions of local or generalized inflammation (during peritonitis and sepsis), reverting to normal num bers within 14 days after the acute phase of the episode [10,11].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although their physiological significance is less clear, the working hypothesis is that they retard the passage of molecules of similar charge a n d /o r accelerate that of molecules with opposite polarity. This is certainly true of anionic charges on glomerular and intestinal capillaries [5][6][7], Previous studies in our laboratory showed the exis tence of anionic charges on the peritoneal basement membrane and capillaries subjacent to it [8,9]. Recently we demonstrated that these charges are greatly reduced under conditions of local or generalized inflammation (during peritonitis and sepsis), reverting to normal num bers within 14 days after the acute phase of the episode [10,11].…”
Section: Introductionmentioning
confidence: 81%
“…Anionic charges are present at the various levels of the peritoneal barrier: microvilli, basement membrane, ca pillaries [8,9], Inflammatory mediators like bradykinin and histamine have little effect on urea clearance across it [36] and the polycation polyethyleneimine increases only water transport [37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the existence of continu ous electronegative charges along the mesothelial cell glycocalyx as well as along the basement membrane of both peritoneal mésothélium [18][19][20] and that of submesothelial capillaries and postcapillary venules [18,21], as well as a substantial reduction of the AS density distribu tion in mesenteric and diaphragmatic microvessels as a consequence of murine experimental septic peritonitis [22]. Therefore, a substantial reduction of the electrone gative charge of the microvascular and mesothelial bar riers could be a rational pathophysiological explanation for the increased protein losses observed during peritoni tis.…”
Section: Introductionmentioning
confidence: 99%
“…Injury to the mesothelium represents an important initiating step, leading to the progressive histologic changes of the peritoneum in peritoneal dialysis (PD). The abundant anionic sites normally present in the mesothelium and the underlying basement membrane prevent excessive albumin wastage (5)(6)(7)(8). Proteoglycans (PG), which are anionic macromolecules present ubiquitously on the cell surface and in basement membrane (9,10), are putatively major contributors to the anionic sites in the peritoneum.…”
mentioning
confidence: 99%